The Effect of Physical Activity on Blood Pressure in the Community of Tumbang Tahai District, Palangka Raya, Indonesia - Anwar, Muhammad Naufa; Hartoyo, Riccardo; Sandhikarana, I Dewa Gede; Widhiyanto, Hendrykus Theo Damar; Praja, Rian Ka (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: Cardiovascular diseases, including hypertension, pose significant health challenges globally. Physical activity has long been recognized as a modifiable factor that can influence various aspects of cardiovascular health, including blood pressure. However, the relationship between physical activity and blood pressure is complex and can be influenced by various factors such as cultural and regional differences. Aims: The primary objective of this research was to examine the association between physical activity and blood pressure using a quasi-experimental design. Methods: This study utilized a quasi-experimental design with a one-group pre-test post-test approach. The sample was selected using a total sampling technique. The independent and dependent variables in this research were physical activity and blood pressure. Data collection instruments employed in this study consisted of observation sheets, an aneroid sphygmomanometer, and a stethoscope. Data analysis was performed using the Wilcoxon test. Results: This study showed that there was an association between physical activity and blood pressure. Conclusion: this research sheds light on the relationship between physical activity and blood pressure. The findings underscore the importance of considering cultural and regional factors in designing health interventions. Received: 20 November 2023, Reviewed: 21 November 2023, Revised: 14 March 2024, Accepted: 03 April 2024.